2011
DOI: 10.1007/s10096-011-1479-4
|View full text |Cite
|
Sign up to set email alerts
|

Signs and symptoms predicting influenza in children: a matched case–control analysis of prospectively collected clinical data

Abstract: We aimed to determine whether there are signs or symptoms that could help clinicians to distinguish between influenza and other respiratory infections. The clinical data for this matched case-control analysis were derived from a 2-year prospective cohort study of respiratory infections among children aged≤13 years. At any signs of respiratory infection, the children were examined and nasal swabs were obtained for virologic analyses. Cases were 353 children with laboratory-confirmed influenza and controls were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
7
21
1
Order By: Relevance
“…The variety of other potential co-infecting pathogens may have caused the lower performance of all case definitions in the 0–4 years age group [10]. One way to improve the specificity of the ILI definition in this particular age group would be a higher temperature cut-off because the multivariate model showed that in the youngest age group, only high body temperatures above 38.5 °C were strongly associated with influenza.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variety of other potential co-infecting pathogens may have caused the lower performance of all case definitions in the 0–4 years age group [10]. One way to improve the specificity of the ILI definition in this particular age group would be a higher temperature cut-off because the multivariate model showed that in the youngest age group, only high body temperatures above 38.5 °C were strongly associated with influenza.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal case definition should be applicable every year, internationally and in all medical settings (i.e community, outpatient and inpatient departments), regardless of the patients’ age or co-infections with co-circulating respiratory viruses such as respiratory syncytial virus (RSV) or rhinovirus [1]. Several previous studies have attempted to evaluate and compare the performance of the current ILI definitions, but are restricted either to a single hospital setting [3-8] or to cohort studies [9,10]. Only few studies have evaluated the performance of the current ILI/ARI definitions in the context of a national influenza sentinel network over several years [11,12] and none included a paediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of clinical syndromes are associated with the common respiratory viruses, including the common cold, pharyngitis, laryngitis, influenza-like illness, laryngeotracheobronchitis (croup), bronchiolitis, and pneumonia. Certain viruses are often associated with specific syndromes and age groups ( Table 2), although clinical disease is commonly overlapping and each syndrome can be caused by many different respiratory viruses (68,69). RSV is the single most important agent of respiratory disease in infancy and is the most common cause of bronchiolitis and pneumonia in infants and young children worldwide (26,27,70,71).…”
Section: Clinical Significancementioning
confidence: 99%
“…The clinical diagnosis of respiratory viruses can be difficult, since signs and symptoms are often overlapping and not always specific for any one viral agent (68,69) when multiple pathogens are circulating in a given community, as is the case in the fall-winter-spring seasonal activity observed in most cities throughout the U.S. and other parts of the world. Clinical findings may vary with age, underlying conditions of the host, previous infection, and the circulating type, and may fail to identify the persons at highest risk for complications.…”
Section: Diagnostic Approachesmentioning
confidence: 99%
“…A Finnish group who used a matched case-control study in children aged ≤13 years to compare confirmed influenza patients with those who had respiratory symptoms but were influenza-negative found fever to be the only reliable predictor of influenza [54]. …”
Section: Clinical Manifestations Of Diseasementioning
confidence: 99%